RELEVANSI PEMIKIRAN PENDIDIKAN IMAM AL-GHAZALI TERHADAP PENDIDIKAN AGAMA ISLAM DI SMAN 1 TANAH JAWA KECAMATAN TANAH JAWA KABUPATEN SIMALUNGUN PADA ERA MILENIAL - Pramustika, Anisyah (Fakultas Agama Islam, 2023)
Education is an effort to prepare students to be able to carry out roles that require mastery of knowledge. According to Imam Al-Ghazali, true education is a means of getting closer to Allah SWT. Education leads people to achieve happiness in this world and the hereafter, as well as a means of spreading virtue. This research aims: